2016
DOI: 10.1016/j.vetmic.2015.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular investigations on the prevalence and viral load of enteric viruses in pigs from five European countries

Abstract: Enteric viral infections in pigs may cause diarrhea resulting in ill-thrift and substantial economic losses. This study reports the enteric infections with porcine astrovirus type 4 (PAstV4), porcine group A rotavirus (GARV), porcine group C rotavirus (GCRV), porcine circovirus type 2 (PCV2) and porcine kobuvirus (PKoV) in 419 pigs, comprising both healthy and diarrheic animals, from 49 farms in five European countries (Austria, Germany, Hungary, Spain and Sweden). Real-time RT-PCR assays were developed to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
75
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 40 publications
11
75
1
Order By: Relevance
“…PCV2 frequencies reported over last (Sun et al, 2015), while another work, in Japan found 80% of positive tonsil samples collected from pigs aged 6 months (Saekhow et al, 2015). Our results showed that PCV2 was detected in all states, with a frequency of 57% of positive herds, and 49% of positive animals, in five European countries 42% of fecal samples taken from both healthy and diarrheic pigs were positive and the percentage was higher in healthy compared to diseased animals (Zhou et al, 2016), which suggest that most PCV2 infections were subclinical. In our study only samples from diseased animals were included; it could produce very interesting results to include also healthy animals to determine total and subclinical frequencies.…”
Section: Resultssupporting
confidence: 50%
“…PCV2 frequencies reported over last (Sun et al, 2015), while another work, in Japan found 80% of positive tonsil samples collected from pigs aged 6 months (Saekhow et al, 2015). Our results showed that PCV2 was detected in all states, with a frequency of 57% of positive herds, and 49% of positive animals, in five European countries 42% of fecal samples taken from both healthy and diarrheic pigs were positive and the percentage was higher in healthy compared to diseased animals (Zhou et al, 2016), which suggest that most PCV2 infections were subclinical. In our study only samples from diseased animals were included; it could produce very interesting results to include also healthy animals to determine total and subclinical frequencies.…”
Section: Resultssupporting
confidence: 50%
“…A possible pathogenic role for PAstV4 is therefore also conceivable alone or in concert with PCV3. PAstV4, first sequenced in Hungarian pig feces in 2011 [32], are a diverse group of related viruses that can be detected in the feces of 70 % of European pigs tested with higher viral loads in some age groups of diarrheic pigs [33] and may be associated with diarrhea in pigs from Minnesota [34]. PAstV4 was also detected in the blood of healthy pigs from Croatia [35].…”
Section: The Studymentioning
confidence: 99%
“…Some studies showed PKV had significantly higher prevalence in diarrhoeic pigs than healthy pigs in Hungary, Spain, South Korea, China and Brazil (Barry, Ribeiro, Alfieri, van der Poel, & Alfieri, ; Park et al., ; Wang, Lan, & Hua, ; Zhou et al., ). Several studies suggested that there was no significance in the incidence of PKV among pigs with diarrhoea and healthy pigs in Slovakia, Austria and USA (Jackova et al., ; Verma, Mor, Abdel‐Glil, & Goyal, ; Zhou et al., ). Even more surprising is that PKV had significantly higher prevalence in healthy pigs than diarrhoeic pigs in Sweden and South Korea (An et al., ; Zhou et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies suggested that there was no significance in the incidence of PKV among pigs with diarrhoea and healthy pigs in Slovakia, Austria and USA (Jackova et al., ; Verma, Mor, Abdel‐Glil, & Goyal, ; Zhou et al., ). Even more surprising is that PKV had significantly higher prevalence in healthy pigs than diarrhoeic pigs in Sweden and South Korea (An et al., ; Zhou et al., ). In addition, PKV co‐infected by porcine epidemic diarrhoea virus, porcine transmissible gastroenteritis virus, porcine astrovirus, porcine rotavirus A, porcine circovirus type 2 was reported in several studies (Dufkova, Scigalkova, Moutelikova, Malenovska, & Prodelalova, ; Jackova et al., ; Park et al., ; Reuter et al., ; Verma et al., ; Zhou et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation